Use of traffic crash as a risk assessment scale in hospitalized seniors: a perspective observational study - Guasconi, Massimo; Pisaroni, Nicola; Bertuol, Maria; Scazzariello, Martina; Delfino, Federica; Bolzoni, Marina; Grossi, Cinzia Franca; Beretta, Maurizio; Marchetti, Annalisa; Boselli, Andrea; Sarli, Leopoldo; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: According to the World Health Organization (WHO), falls represent the second main cause of accidental and involuntary deaths worldwide, which led to define them as one of the “four giants of the geriatrician” that particularly affect the elderly aged ≥ 65 years. The study’s aim is to evaluate whether the Traffic Crash scale is valid in identifying patients at risk of falling by comparing it to the Conley scale currently used. Methods: Prospective observational study evaluating the fall risk using TC on a sample of patients aged ≥ 65 years, hospitalized in General Medicine Ward and Gastroenterology, after informed consent and favorable opinion of the AVEN Ethics Committee. The results are compared with those obtained from the Conley scale, and with those obtained from the indications of the Business Operating Instruction. The method of administration occurred concurrently and distinctly on the same patient by two researchers in order to demonstrate the scale inter-rater reliability. Results: The final sample was made up of 88 patients. Data shows that 46 out of 55 patients (84%) are medium / high risk for both scales. According to the indications of the Company Operating Instruction, the entire sample is at risk. The inter-rater reliability was confirmed with Cohen’s K which is equal to p = 1. Conclusions: The TC scale is comparable to Conley scale, for the fall risk identification but specifically the stratification is low-medium-high. Therefore, in future, this will make it possible to implement personalized prevention interventions in care planning.